2012
DOI: 10.4103/0974-1208.106338
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene citrate or letrozole as first-line ovulation induction drug in infertile PCOS women: A prospective randomized trial

Abstract: OBJECTIVE:To compare Letrozole (5 mg) and clomiphene citrate (100 mg) as first line ovulation induction drug in infertile PCOS women.STUDY DESIGN:Prospective Randomised trial.SETTING:A Tertiary level infertility centre. Patients: 103 infertile PCOS womenINTERVENTION(S):Treatment naïve infertile PCOS women were randomised to treatment with 5 mg letrozole (51 patients) or 100 mg clomiphene citrate (52 patients) daily starting day 2 to day 6 of menstrual cycle. Timed intercourse or Intra Uterine Insemination (IUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 20 publications
8
61
4
2
Order By: Relevance
“…These findings are in agreement with clinical evidence supporting a direct role for androgen actions in the development of dysfunctional menstrual cycling and ovulation in PCOS, as prolonged treatment with the AR antagonist flutamide is reported to restore menstrual-cycle regularity and ovulation in some women with PCOS (15,29). Interestingly, by contrast, the treatment of women with PCOS with estrogen blockage, either by antiestrogen (clomiphene citrate) or an aromatase inhibitor (letrozole) that increases FSH secretion, is rapidly effective at inducing ovulation (30). This implies that the hypothalamic-pituitary feedback response in PCOS women is functional but that the longer time to effective treatment by androgen blockade may involve more complex, possibly multistep underlying mechanisms of androgen-mediated effects, compared with the more direct mode of action of estrogen blockade.…”
Section: Discussionsupporting
confidence: 71%
“…These findings are in agreement with clinical evidence supporting a direct role for androgen actions in the development of dysfunctional menstrual cycling and ovulation in PCOS, as prolonged treatment with the AR antagonist flutamide is reported to restore menstrual-cycle regularity and ovulation in some women with PCOS (15,29). Interestingly, by contrast, the treatment of women with PCOS with estrogen blockage, either by antiestrogen (clomiphene citrate) or an aromatase inhibitor (letrozole) that increases FSH secretion, is rapidly effective at inducing ovulation (30). This implies that the hypothalamic-pituitary feedback response in PCOS women is functional but that the longer time to effective treatment by androgen blockade may involve more complex, possibly multistep underlying mechanisms of androgen-mediated effects, compared with the more direct mode of action of estrogen blockade.…”
Section: Discussionsupporting
confidence: 71%
“…Metformin does not have an effect on the biochemical parameters of FSH, LH. This differs from some studies showing that metformin reduces the effect of LH and causes an elevation in serum FSH [29] [30] and agreed with studies showing that metformin has no effect on hormonal parameters [20] [31] [32]. Historically, the overall successful pregnancy rates after ovulation induction range from as low as 9% to as high as 25% [33].…”
Section: Discussioncontrasting
confidence: 53%
“…However, clinical trials of aromatase inhibitors for PCOS yield controversial results regarding pregnancy rates (Badawy et al 2009, Kar 2012, Roy et al 2012). The present study has shown that aromatase expression in luteinized granulosa cells is down-regulated by high testosterone in PCOS patients.…”
Section: Discussionmentioning
confidence: 99%